Scratch-resistant water-based gravure gloss oil as well as preparation method and application thereof
By using a specific ratio of styrene-acrylate copolymer and water-based polyurethane dispersion in water-based varnish as film-forming resin, the problem of insufficient scratch resistance of water-based varnish in packaging printing is solved, and high gloss is achieved And excellent scratch resistance, friction resistance and anti-adhesion properties.
Patent Information
- Application Number
- CN202411475924.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
Smart Images

Figure BDA0005096103690000121 
Figure BDA0005096103690000131 
Figure BDA0005096103690000132
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water-based inks, and in particular to a water-based gravure varnish and a preparation method thereof. Background Art
[0002] Varnish is a decorative and protective coating applied to printed paper, film or leather substrates. The application of varnish coating can not only enhance the brightness and protect the printed images, but also does not affect the recycling of paper, which can save resources and protect the environment. Therefore, varnish is widely used in the surface treatment of packaging printed products.
[0003] Most traditional varnishes are solvent-based varnishes, which cannot meet the current environmental protection requirements. Water-based varnishes mainly use water as a solvent, and are widely used due to their many advantages such as being non-toxic, odorless, safe and environmentally friendly. At present, the main resin of most water-based varnishes is water-based acrylic resin. However, water-based acrylic resins have the problems of being hot-sticky and cold-brittle, as well as poor water resistance and poor adhesion to certain substrates. Moreover, water-based varnishes are easily scratched or scratched after film formation, and fine packaging printing will have subsequent processes such as hot stamping, die-cutting, and bonding. Scratches and scratches on the surface of the varnish will affect subsequent processes. At present, the problem of water-based varnishes not being resistant to scratches has greatly troubled the printing industry, seriously affecting the use of water-based varnishes in packaging printing.
[0004] The invention patent with application number CN202010343483.0 discloses a water-based thin film gravure composite ink, which includes a water-based resin, a pigment, a wetting agent, a defoamer, and a dispersion medium component, wherein the water-based resin is a water-based polyurethane resin and a water-based acrylic resin, and the dispersion medium is water and ethanol. It combines water-based polyurethane with water-based acrylic resin to reduce costs and improve the surface adhesion ability, peel strength and other properties of the ink. However, the proportion of water-based polyurethane in the ink formula of this invention is relatively high, resulting in a higher cost of the ink, and the invention does not pay attention to the scratch resistance of the ink.
[0005] The invention patent with application number CN202010653620.0 discloses a water-based varnish, which improves the anti-adhesion and wear resistance of the varnish by adding fluorinated olefin monomers and triallyl isocyanurate monomers during the preparation of the styrene-acrylate emulsion, a film-forming resin of the varnish. However, the fluorinated olefin monomers in the invention are all toxic gases, there are major safety hazards in the preparation process of the film-forming emulsion, and the preparation process is complicated. In addition, the introduction of fluorinated monomers into the film-forming resin will reduce the surface energy of the varnish and deteriorate the wettability of the substrate, which limits the application of the varnish.
[0006] The invention patent with publication number CN106519796A discloses a highly scratch-resistant water-based transparent ink, whose film-forming resin package is composed of a multifunctional styrene-acrylic copolymer emulsion and a high molecular weight solid acrylic resin, and the multifunctional styrene-acrylic copolymer emulsion is a styrene-acrylic copolymer soft emulsion and a styrene-acrylic copolymer hard emulsion. The invention is to improve the scratch resistance by forming a high crosslinking density with a multifunctional styrene acrylic copolymer emulsion to increase the hardness of the ink. At the same time, nano-silicon dioxide is added to assist in improving the scratch resistance. It can be seen that the invention is essentially to improve the scratch resistance by increasing the hardness of the varnish coating. However, the hardness of the varnish coating is relatively large, and the scratches are difficult to repair after being scratched. Moreover, the addition of inorganic nano-silicon dioxide in the coating will reduce the gloss of the varnish and also make the tactile feel of the coating worse, making it difficult to obtain a coating with a good feel.
[0007] The invention patent with application number CN201810271473.3 discloses a water-based varnish for Polaroid paper, which is composed of 50-68 parts of silicone-acrylic emulsion, 5-8 parts of wax additive, 0.5-2 parts of hand feeling agent, 0.05-0.15 parts of wetting agent, 10-17 parts of low molecular alcohol, and 15.9-22.95 parts of deionized water. The silicone-acrylic emulsion is a self-made silicone-acrylic emulsion with a unique structure of "internal cross-linked core-silicon-containing shell" as a film-forming resin for water-based varnish. The resulting varnish coating has good anti-adhesion, tape peeling resistance and oil stain resistance. However, the varnish has poor versatility and high cost.
[0008] The invention patent with application number CN202111273507.0 discloses a water-based gravure pre-printing varnish, which includes components such as film-forming high-temperature resistant styrene-acrylic emulsion, soft film-forming high-temperature resistant styrene-acrylic emulsion, hard non-film-forming high-temperature resistant styrene-acrylic emulsion, and quick-drying modified maleic anhydride resin liquid A. The varnish includes a large amount of non-film-forming resin components, and the resulting varnish has a low gloss and poor film-forming density.
[0009] On the other hand, in the art, anti-scratch agents, such as high molecular weight polysiloxane DC-51, are usually added to improve the anti-scratch and anti-mark effects of varnish. However, adding anti-scratch agents to varnish often results in a decrease in the surface dyne value of the varnish, affecting the recoatability of the varnish film. Moreover, anti-scratch agents are often difficult to disperse, which can easily cause shrinkage holes in the varnish film and poor leveling properties. Summary of the invention
[0010] In order to overcome the shortcomings and deficiencies of the above-mentioned prior art, the present invention discloses a scratch-resistant water-based varnish and a preparation method thereof. The scratch-resistant water-based varnish obtained by the present invention does not need to add anti-scratch or anti-scratch additives, and the obtained varnish coating has high gloss, good friction resistance and anti-adhesion properties, and scratch resistance, and has good freeze-thaw stability and high-temperature storage stability.
[0011] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0012] A scratch-resistant water-based gravure varnish, characterized in that it comprises the following components by mass percentage:
[0013] Mixed resin 10%-80%, non-ionic surfactant 1-3%, defoaming agent 0.01-0.2%, ethanol 1-5%, and deionized water as the balance.
[0014] The sum of the mass percentages of the above-mentioned varnish components is 100%.
[0015] Furthermore, the mass percentage of the mixed resin is 30-80%.
[0016] The solid content of the mixed resin is 25-50%.
[0017] The mixed resin includes styrene-acrylate copolymer A, styrene-acrylate copolymer B and waterborne polyurethane dispersion.
[0018] In the mixed resin, based on the mass percentage of non-volatile components, the styrene-acrylate copolymer A accounts for 15-45%, the styrene-acrylate copolymer B accounts for 45-75%, and the waterborne polyurethane dispersion accounts for 10-40%.
[0019] The Tg of the styrene-acrylate copolymer A is 80-120°C. The Tg of the styrene-acrylate copolymer B is <-20°C.
[0020] The Tg of the styrene-acrylate copolymer A and the styrene-acrylate copolymer B can be obtained by testing their dry films using a differential scanning calorimeter (DSC).
[0021] The styrene-acrylate copolymer A and the styrene-acrylate copolymer B can be purchased from the market or prepared by oneself, and the sources of the two are not limited in the present invention.
[0022] For commercially available products, the styrene-acrylate copolymer A can be selected from JONCRYL 61, JONCRYL HPD96, JONCRYL 354, and JONCRYL DFC3025. The styrene-acrylate copolymer B can be selected from JONCRYL 624, JONCRYL 1695, and JONCRYL 8052.
[0023] For self-production, the glass transition temperature and the minimum film forming temperature of the styrene-acrylate copolymer can be adjusted by adjusting the ratio of the polymerized soft monomer and the hard monomer, which is well known to those skilled in the art. The styrene-acrylate copolymer is obtained by an emulsion polymerization process, and the solid content of the styrene-acrylate copolymer emulsion is 30-50wt%.
[0024] The nonionic surfactant is a fatty alcohol polyoxyethylene ether type nonionic surfactant.
[0025] The waterborne polyurethane dispersion is homemade, and its preparation raw materials include polymer diol, diisocyanate, single-end dihydroxy polysiloxane, carboxylate type hydrophilic chain extender, sulfonate type hydrophilic chain extender, amine chain extender, surfactant, organic amine neutralizer and deionized water.
[0026] The average particle size of the aqueous polyurethane dispersion is 50-120 nm, and the solid content is 30-50%.
[0027] The polymer diol has a number average molecular weight of 1500-2000 g / mol (for example, may be or be about 2000 g / mol); the type of the polymer diol is one or more of polycarbonate diol, polycaprolactone diol, and aromatic polyester diol.
[0028] The diisocyanate is one or more of isophorone diisocyanate, hexamethylene diisocyanate, and 4,4-dicyclohexylmethane diisocyanate.
[0029] Furthermore, the diisocyanate is preferably 4,4-dicyclohexylmethane diisocyanate.
[0030] The selection of the single-ended dihydroxy polysiloxane is not limited, and common choices include Shin-Etsu X-22-176DX and X-22-176GX-A.
[0031] The mass proportion of the single-terminal dihydroxy polysiloxane in the solid content of the polyurethane dispersion is 2-5%.
[0032] The carboxylate type hydrophilic chain extender is dimethylol propionic acid, the sulfonate type hydrophilic chain extender is sodium ethylenediamine ethanesulfonate, and the organic amine neutralizer is triethylamine or N,N-dimethylethanolamine.
[0033] The mass proportion of the carboxylate type hydrophilic chain extender in the solid content of the polyurethane dispersion is 3.5-5.5%.
[0034] The mass proportion of the sulfonate type hydrophilic chain extender in the solid content of the polyurethane dispersion is 0.2-0.6%.
[0035] The surfactant is at least one of an anionic surfactant and a nonionic surfactant. The HLB of the surfactant is in the range of 14 to 24.
[0036] Preferably, the surfactant is a nonionic surfactant. Common brands of the surfactant are Clariant LCN287, LCN070, and LCN407.
[0037] The mass proportion of the surfactant in the solid content of the polyurethane dispersion is 0.2-0.8%.
[0038] Furthermore, the mass proportions of the single-ended dihydroxy polysiloxane, carboxylate type hydrophilic chain extender, sulfonate type hydrophilic chain extender, and surfactant in the solid content of the polyurethane dispersion are all the mass proportions of the effective ingredients or non-volatile components of the above raw materials in the solid content of the polyurethane dispersion.
[0039] The amine chain extender is one or more of 1,4-cyclohexanediamine, diethyltriamine and triethyltetramine.
[0040] Furthermore, the amine chain extender is preferably diethyltriamine or a combination of diethyltriamine and 1,4-cyclohexanediamine.
[0041] A method for preparing a scratch-resistant water-based gravure varnish, characterized in that it comprises the following steps:
[0042] Step 1: preparing styrene-acrylate copolymer A, styrene-acrylate copolymer B, and waterborne polyurethane dispersion;
[0043] Step 2: adding styrene-acrylate copolymer A, styrene-acrylate copolymer B, and aqueous polyurethane dispersion into a pull cylinder, dispersing (for example, dispersing at a low speed) to obtain a mixed resin;
[0044] Step 3: Under dispersed conditions, add nonionic surfactant to the mixed resin, disperse for 5-10 minutes, add defoamer and ethanol within 5-15 minutes, and then adjust the solid content to the set value with deionized water;
[0045] Step 4: Stop dispersing, let stand, and sieve through filter cloth (for example, 400 mesh filter cloth can be used for sieving), to obtain a finished water-based gravure varnish.
[0046] The solid content of the finished water-based gravure varnish is 10-35%, and the pH is 6-9, both of which can be adjusted by ordinary technicians in this field according to application requirements.
[0047] Furthermore, the preparation of the aqueous polyurethane dispersion comprises the following steps:
[0048] Step (1): prepare various raw material components, add polymer diol, single-end dihydroxy polysiloxane, and carboxylate type hydrophilic chain extender into a reaction kettle, start stirring, raise the temperature to 115-125° C. (for example, 120° C.), evacuate, dehydrate, and cool to 45-55° C. (for example, 50° C.);
[0049] Step (2): add diisocyanate to the reaction kettle, raise the temperature to 75-85° C. (e.g., 80° C.) and react for 2-5 hours;
[0050] Step (3): cooling to 45-55° C. (e.g., 50° C.), adding an organic amine neutralizer, and reacting for 20-40 minutes to obtain a neutralized prepolymer;
[0051] Step (4): adding deionized water containing a surfactant and a sulfonate-type hydrophilic chain extender to the neutralized prepolymer, dispersing (for example, high-speed dispersion) for 5 to 10 minutes to obtain a dispersion;
[0052] Step (5): adding an amine chain extender to the dispersion and continuing to disperse for 5 to 10 minutes to obtain an aqueous polyurethane dispersion.
[0053] The beneficial effects of the present invention are as follows:
[0054] The invention selects a high-Tg styrene-acrylate copolymer A, a low-Tg styrene-acrylate copolymer B, and an aqueous polyurethane dispersion which is wear-resistant, has both hardness and adhesion and contains branched polysiloxane as film-forming resin components of the aqueous gravure varnish. Without adding an anti-scratch or anti-abrasion auxiliary agent, the obtained aqueous gravure varnish has good storage stability, and the coating has high gloss, good hand feel, and excellent properties such as friction resistance, anti-adhesion, and scratch resistance. DETAILED DESCRIPTION
[0055] The present invention will be further described below in conjunction with specific embodiments:
[0056] It should be understood that the specific embodiments described herein are part of the embodiments of the present invention, rather than all of the embodiments, and are merely used to explain the embodiments of the present invention, and are not used to limit the embodiments of the present invention. All other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0057] The selection of raw materials in the following examples and comparative examples is as follows:
[0058] (1) Styrene-acrylate copolymer
[0059] Styrene-acrylate copolymer A: JONCRYL 61 has a solid content of about 36% and a Tg of about 85°C; JONCRYL HPD96 has a solid content of about 34% and a Tg of about 88°C; JONCRYL 354 has a solid content of about 32% and a Tg of about 101°C.
[0060] JONCRYL LMV7085 has a solid content of about 35% and a Tg of about 77°C (for comparison). The above raw materials were obtained from BASF.
[0061] The styrene-acrylate copolymer B: JONCRYL 624 has a solid content of about 48% and a Tg of about -30°C; JONCRYL 1695 has a solid content of about 40% and a Tg of about -50°C; JONCRYL 8052 has a solid content of about 47% and a Tg of about -35°C.
[0062] JONCRYL 2640 has a solid content of about 49% and a Tg of about -18°C (for comparison). The above raw materials were obtained from BASF.
[0063] Nonionic surfactant: Clariant LCN287, ethanol were purchased from the market.
[0064] (2) Waterborne polyurethane dispersion
[0065] PCD-2000, Ube, Japan; 4,4-dicyclohexylmethane diisocyanate (HMDI), Evonik; single-end dihydroxy polysiloxane, Shin-Etsu X-22-176DX; dimethylol propionic acid (DMPA), Perstorp; surfactant Clariant LCN287; triethylamine, sodium ethylenediamine sulfonate, 1,4-cyclohexanediamine, and diethyltriamine were all commercially available.
[0066] Synthesis example 1
[0067] Aqueous polyurethane dispersion A, the preparation method thereof is as follows:
[0068] Step (1): by weight, add 100 parts of PCD-2000, 5 parts of single-end dihydroxy polysiloxane X-22-176DX, and 7 parts of DMPA into a reaction kettle, stir at 120 rpm, heat to 120° C., evacuate, dehydrate, and cool to 50° C.;
[0069] Step (2): add 48.3 parts of diisocyanate HMDI into the reaction kettle, raise the temperature to 80°C and react for 4 hours;
[0070] Step (3): cooling to 50° C., adding 5.2 parts of a neutralizing agent, triethylamine, and reacting for 20 minutes to obtain a neutralized prepolymer;
[0071] Step (4): adding 1 part of surfactant LCN287, 1.2 parts of sodium ethylenediamine sulfonate and 250 parts of deionized water to the neutralized prepolymer, and dispersing at a high speed of 1200 rpm for 5 minutes to obtain a dispersion;
[0072] Step (5): add 2 parts of diethylenetriamine and 5.2 parts of 1,4-cyclohexanediamine to the dispersion, continue dispersing at 300 rpm for 5 minutes, add an appropriate amount of deionized water, adjust the solid content to 32%, and obtain an aqueous polyurethane dispersion.
[0073] Among them, the surfactant LCN287 accounts for about 0.4% of the solid weight of the aqueous polyurethane dispersion, the sulfonic acid type hydrophilic chain extender sodium ethylenediamine ethanesulfonate accounts for about 0.34% of the solid weight, the carboxylic acid type hydrophilic chain extender DMPA accounts for about 4.0% of the solid weight, and the single-end dihydroxy polysiloxane accounts for about 2.9% of the solid weight.
[0074] Synthesis example 2
[0075] Aqueous polyurethane dispersion B was prepared in accordance with Preparation Example 1, but without adding surfactant LCN287 during the dispersion process.
[0076] Synthesis example 3
[0077] Aqueous polyurethane dispersion C is prepared in Example 1, except that the sulfonic acid type hydrophilic chain extender sodium ethylenediamine ethanesulfonate is not added during the dispersion process, and an equal molar amount of DMPA is used to replace the active ingredient sodium ethylenediamine ethanesulfonate.
[0078] Synthesis example 4
[0079] Aqueous polyurethane dispersion D, based on Preparation Example 1, uses part of sodium ethylenediamine sulfonate to replace 1,4-cyclohexanediamine during the synthesis process, and increases the solid weight of sodium ethylenediamine sulfonate to about 0.8%.
[0080] Synthesis example 5
[0081] Aqueous polyurethane dispersion E, based on Preparation Example 1, during the synthesis process, the single-terminal dihydroxy polysiloxane is increased to account for about 6% of the solid weight. Among them, the surfactant LCN287 accounts for about 0.39% of the solid weight, the sulfonic acid type hydrophilic chain extender sodium ethylenediamine ethanesulfonate accounts for about 0.3% of the solid weight, and the carboxylic acid type hydrophilic chain extender DMPA accounts for about 3.9% of the solid weight.
[0082] Synthesis example 6
[0083] Aqueous polyurethane dispersion F, based on Preparation Example 1, reduces the solid weight of single-terminal dihydroxy polysiloxane to about 1%, wherein the surfactant LCN287 accounts for about 0.4% of the solid weight, the sulfonic acid type hydrophilic chain extender sodium ethylenediamine ethanesulfonate accounts for about 0.35% of the solid weight, and the carboxylic acid type hydrophilic chain extender DMPA accounts for about 4.1% of the solid weight.
[0084] Synthesis Example 7
[0085] Aqueous polyurethane dispersion G is prepared in accordance with Preparation Example 1, except that an equal amount of linear terminal hydroxyl siloxane Dow Corning PMX-0156 is used to replace the single-terminated dihydroxy polysiloxane X-22-176DX during the synthesis process.
[0086] Synthesis example 8
[0087] Aqueous polyurethane dispersion G is prepared in accordance with Preparation Example 1, except that an equal amount of polytetramethylene ether glycol PTMEG2000 is used instead of PCD2000 as the polymer diol during the synthesis process.
[0088] Preparation of water-based gravure ink
[0089] The preparation method is as follows:
[0090] Step 1: Add styrene-acrylate copolymer A, styrene-acrylate copolymer B, and aqueous polyurethane dispersion into a pull cylinder according to the raw materials and dosage of the mixed resin in Table 1, and disperse at a low speed of 120 rpm to obtain a mixed resin; add deionized water to adjust the solid content of the mixed resin to 30%.
[0091] Step 3: Under the condition of low-speed dispersion at 120 rpm, add 1 part of non-ionic surfactant LCN287 to 70 parts of mixed resin with a solid content of 30%, disperse at low speed for 10 minutes, add 0.2 parts of defoamer tego904W and 5 parts of ethanol within 5 minutes, and then adjust the solid content to 25% with an appropriate amount of deionized water;
[0092] Step 4: Stop dispersing, let it stand, and filter it through a 400-mesh filter cloth to obtain a finished water-based gravure varnish.
[0093] Table 1 records the composition and ratio of the mixed resins in the varnishes of different embodiments. The amounts of the styrene-acrylate copolymer and the aqueous polyurethane dispersion are calculated based on the content of the non-volatile components.
[0094] Table 1: Composition and ratio of mixed resin
[0095]
[0096]
[0097] Performance Testing
[0098] High temperature storage stability: Place the finished varnish in a 60°C oven and record the varnish stability status every other day. The test lasts for one month.
[0099] Freeze-thaw stability: Place the finished varnish in a -20℃ freezer and record the stability of the varnish every other day. The test lasts for one month.
[0100] Gloss: Apply varnish on test cardboard and dry at 50℃. The dry film thickness is about 2.5μm. Use a gloss meter to test the 60° gloss value of the varnish dry film.
[0101] Scratch resistance: Tested in accordance with GB / T9279.1-2015, with a weight of 500g.
[0102] Abrasion resistance: Load 9.8N, use dry and wet gauze to wipe the colored varnish coating surface back and forth 10 times, observe the coloring of the gauze surface and score it, 5 points is the best and 1 point is the worst.
[0103] Anti-adhesion performance: Place the varnish coatings on the test cardboard "face to face" and place them under 5Kg pressure and 80℃ temperature conditions for 24 hours.
[0104] Coating appearance: Visually inspect and evaluate the leveling and pinhole conditions on the coating surface, with 5 points being the best and 1 point being the worst.
[0105] The test results are shown in Table 2.
[0106] Table 2: Performance test results
[0107]
[0108]
[0109] From the results in Table 2 above, it can be seen that when styrene-acrylate copolymer in a specific dosage range and a specific Tg range and an aqueous polyurethane dispersion are selected as the mixed film-forming resin of the aqueous varnish, the resulting aqueous varnish has good gloss, storage stability, scratch resistance, friction resistance, anti-adhesion and other application properties.
[0110] The film-forming resin of Comparative Example 1 is a high Tg non-film-forming resin, and no coating can be obtained. The coating obtained from the film-forming resin of Comparative Example 2 is too soft and has poor application performance. Comparative Example 3 uses polyurethane dispersion as the film-forming resin, but the freeze-thaw stability of the varnish is poor, and the friction resistance and anti-adhesion performance are poor. Comparative Example 4 does not contain polyurethane dispersion, and has poor scratch resistance, friction resistance, and anti-adhesion performance. The Tg of the styrene-acrylate copolymer of Comparative Example 5 is not within the range, and the freeze-thaw stability, scratch resistance, friction resistance, and anti-adhesion performance of the obtained varnish do not meet the requirements.
[0111] On the basis of Example 1, the aqueous polyurethane dispersions B to H obtained in Synthesis Examples 2-8 were used to replace the aqueous polyurethane dispersion A obtained in Synthesis Example 1 in the varnish mixed resin. The corresponding aqueous varnishes were marked as Comparative Examples 6 to 12. The corresponding application test results are shown in Table 3.
[0112] Table 3: Performance test results
[0113]
[0114]
[0115] From the above test results, it can be seen that the selection of synthetic raw materials and dosage of waterborne polyurethane dispersion also has a significant impact on the application performance of waterborne varnish.
[0116] In the dispersion process of the aqueous polyurethane dispersion B used in Comparative Example 6, no surfactant was added; in the dispersion process of the aqueous polyurethane dispersion C used in Comparative Example 7, no sodium ethylenediaminesulfonate was added. The particles of the obtained polyurethane dispersion were not stable enough, resulting in poor high and low temperature storage stability of the varnish and increased viscosity of the varnish during storage.
[0117] In the aqueous polyurethane dispersion D used in Comparative Example 8, too much sodium ethylenediaminesulfonate was added during the dispersion process of the synthesis. During the dispersion process of the obtained aqueous polyurethane dispersion, the reaction between the isocyanate group and the amine group was too violent, resulting in the production of more microgel particles, which deteriorated the storage stability and leveling performance of the varnish.
[0118] The aqueous polyurethane dispersion E used in Comparative Example 9 has an excessive amount of single-ended dihydroxy polysiloxane added during the dispersion process of the synthesis, resulting in the formation of a large number of bubbles during the dispersion process. The resulting dispersion has many particles and is difficult to filter, and the corresponding varnish has poor leveling properties during coating.
[0119] The content of the single-terminal dihydroxy polysiloxane added to the aqueous polyurethane dispersion F used in Comparative Example 10 during the dispersion process of the synthesis is too low, and its role is limited, resulting in poor scratch resistance, friction resistance, and anti-adhesion properties of the varnish coating.
[0120] The siloxane added to the aqueous polyurethane dispersion G used in Comparative Example 11 during the dispersion process of the synthesis is linear siloxane, and the siloxane chain segment is embedded in the carbon chain, which cannot effectively play an anti-scratch and anti-sticking effect, and cannot improve the wear resistance and anti-sticking effect of the varnish coating.
[0121] The aqueous polyurethane dispersion H used in Comparative Example 12 uses common PTMEG as the polymer diol, and the anti-blocking and scratch resistance properties of the varnish corresponding to the obtained dispersion are poor, which does not meet the application requirements.
[0122] It can be seen that the present invention selects specific styrene-acrylate copolymer A, styrene-acrylate copolymer B and aqueous polyurethane dispersion as film-forming resins of water-based gravure varnish, so that the varnish can obtain excellent application properties such as anti-scratch and friction resistance without adding wear-resistant additives. In addition, the varnish has high gloss and good storage stability.
[0123] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A scratch-resistant water-based gravure varnish, characterized in that: In terms of mass percentage, it includes the following components: Mixed resin 10% to 80%, non-ionic surfactant 1 to 3%, defoamer 0.01 to 0.2%, ethanol 1 to 5%, and deionized water as the balance; The mixed resin includes styrene-acrylate copolymer A, styrene-acrylate copolymer B and waterborne polyurethane dispersion; The mixed resin includes, by mass percentage of non-volatile components, 15-45% of styrene-acrylate copolymer A, 45-75% of styrene-acrylate copolymer B, and 10-40% of aqueous polyurethane dispersion. The Tg of the styrene-acrylate copolymer A is 80-120°C; the Tg of the styrene-acrylate copolymer B is less than -20°C; The raw materials for preparing the aqueous polyurethane dispersion include polymer diol, diisocyanate, single-end dihydroxy polysiloxane, carboxylate type hydrophilic chain extender, sulfonate type hydrophilic chain extender, amine chain extender, surfactant, organic amine neutralizer and deionized water.
2. The scratch-resistant water-based gravure varnish according to claim 1, characterized in that: The mass proportion of the single-terminal dihydroxy polysiloxane in the waterborne polyurethane dispersion solids is 2-5%, the mass proportion of the carboxylate type hydrophilic chain extender in the polyurethane dispersion solids is 3.5-5.5%, the mass proportion of the sulfonate type hydrophilic chain extender in the polyurethane dispersion solids is 0.2-0.6%, and the mass proportion of the surfactant in the polyurethane dispersion solids is 0.2-0.8%; The mass proportions of the single-terminal dihydroxy polysiloxane, carboxylate type hydrophilic chain extender, sulfonate type hydrophilic chain extender and surfactant in the solid content of the polyurethane dispersion are all the mass proportions of the effective ingredients or non-volatile components in the solid content of the polyurethane dispersion.
3. The scratch-resistant water-based gravure varnish according to claim 1, characterized in that: The polymer diol has a number average molecular weight of 1500-2500 g / mol; the type of the polymer diol is one or more of polycarbonate diol, polycaprolactone diol, and aromatic polyester diol.
4. The scratch-resistant water-based gravure varnish according to claim 1, characterized in that: The diisocyanate is one or more of isophorone diisocyanate, hexamethylene diisocyanate, and 4,4-dicyclohexylmethane diisocyanate.
5. The scratch-resistant water-based gravure varnish according to claim 1, characterized in that: The nonionic surfactant is fatty alcohol polyoxyethylene ether.
6. The scratch-resistant water-based gravure varnish according to claim 1, characterized in that: The carboxylate type hydrophilic chain extender is dimethylol propionic acid, the sulfonate type hydrophilic chain extender is sodium ethylenediamine ethanesulfonate, and the organic amine neutralizer is triethylamine or N,N-dimethylethanolamine.
7. The scratch-resistant water-based gravure varnish according to claim 1, characterized in that: The amine chain extender is one or more of 1,4-cyclohexanediamine, diethyltriamine and triethyltetramine.
8. The method for preparing a scratch-resistant water-based gravure varnish according to claim 1, characterized in that: The steps include: Step 1: preparing an aqueous polyurethane dispersion; Step 2: adding styrene-acrylate copolymer A, styrene-acrylate copolymer B, and aqueous polyurethane dispersion into a pull cylinder, dispersing, and obtaining a mixed resin; Step 3: Under dispersed conditions, add nonionic surfactant to the mixed resin, disperse for 5-10 minutes, add defoamer and ethanol within 5-15 minutes, and then adjust the solid content to the set value with deionized water; Step 4: Stop dispersing, let it stand, and sieve it through filter cloth to obtain the finished water-based gravure varnish.
9. The method for preparing a scratch-resistant water-based gravure varnish according to claim 8, characterized in that: The preparation of the aqueous polyurethane dispersion comprises the following steps: Step (1): adding polymer polyol, single-terminal dihydroxy polysiloxane, and carboxylate type hydrophilic chain extender into a reaction kettle, stirring, heating to 115-125° C., evacuating, dehydrating, and cooling to 45-55° C.; Step (2): Add diisocyanate to the reaction kettle, raise the temperature to 75-85°C and react for 2-5 hours; Step (3): cooling to 45-55° C., adding an organic amine neutralizer, and reacting for 20-40 minutes to obtain a neutralized prepolymer; Step (4): adding deionized water containing a sulfonate-type hydrophilic chain extender and a surfactant to the neutralized prepolymer and dispersing for 5-10 minutes to obtain a dispersion; Step (5): adding an amine chain extender to the dispersion and continuing to disperse for 5-10 minutes to obtain an aqueous polyurethane dispersion.
10. Use of a scratch-resistant water-based gravure varnish according to any one of claims 1 to 7, characterized in that: Used for surface coating of paper, film and leather.
Citation Information
Patent Citations
Water-borne transparent oil with high scratch resistance and preparing method thereof
CN106519796A
A water-based varnish for Poly paper and its preparation method
CN108410263B
A water-based varnish and its preparation process
CN111876019B
A water-based gravure pre-printing varnish and its preparation method
CN113897094B
Plastic-film water intaglio printing ink
CN101029194A